Family: Foundation of Children's Education in the Era of Qur'anic Disruption - Anisatul Mardiah; Eko Zulfikar; Deddy Ilyas; John Supriyanto; Apriyanti Apriyanti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This article aims to examine the role of the family in educating children in the era of Al-Qur'an-based digital disruption. This is based on the fact that changes in the era of digital disruption can affect the behavior and character of a child who is in the process of finding his identity. By using pure literature research and descriptive data analysis techniques, this article concludes that the role of the family in children's education is crucial to their growth and development. Families must strive to educate, direct, and project each child to fill their lives with solid beliefs so that they consistently carry out Islamic law and are saved from all calamities in this world and the hereafter. There are at least five roles of the family in educating children in the era of Al-Qur'an-based disruption that deserves attention, namely: as the foundation of religion, as forming the character of children, influencing children's self-confidence, instilling mutual respect, and being able to improve achievement in school. Of course, these five roles can be used as guidelines for every family in educating their children based on the Koran in the era of digital disruption